Hubungan Gaya Belajar Dengan Literasi Digital Pada Materi Sel Siswa Kelas XI IPA DDI Alliritengae Maros - Muliana Mada Ali; Rizki Amalia Nur (CV. Insight Publisher, 2023)
This research is a quantitative ex post facto method with a questionnaire method which aims to determine whether or not there is a relationship between learning styles and digital literacy in class XI IPA MA DDI Alliritengae Maros cell material. Class XI IPA 1 and class XI IPA 2 use the same method. The instrument used was a questionnaire in which the statement items amounted to 20 validated statement items. The data analysis technique used was descriptive statistical analysis and inferential statistical analysis using SPSS version 25. The learning style questionnaire was analyzed with an average value of 58.53 and a standard deviation of 4.159, while the digital literacy questionnaire had an average value of 55.70 and a standard deviation of 5.433. Based on the results of the correlation hypothesis test, it was obtained sig (2-tailed) 0.003 <0.05. So, it can be concluded that there is a relationship between learning styles and digital literacy in class XI IPA MA DDI Alliritengae Maros cell material.